Communautés paysannes et systèmes agraires dans une haute vallée andine (Pérou) - José Carlos Barrio de Pedro (Caravelle)
To characterize the agrarian systems of a high Andean valley, 32 peasant communities are grouped into six types based on the composition of their resources (agro-pastoral production areas). There are oppositions between altitude and bottom valley, agriculture (rainfed, irrigated) and livestock (wool, milk), diversification and specialization, etc. The access of the familial production units to the production areas and to livestock confirms the partition of communities and clarifies the situations of transition. The information provided by this study improves our understanding of the social and economic context of peasant communities concerned.